Simplifying
2x + -10 = 10 + -3x
Reorder the terms:
-10 + 2x = 10 + -3x
Solving
-10 + 2x = 10 + -3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '3x' to each side of the equation.
-10 + 2x + 3x = 10 + -3x + 3x
Combine like terms: 2x + 3x = 5x
-10 + 5x = 10 + -3x + 3x
Combine like terms: -3x + 3x = 0
-10 + 5x = 10 + 0
-10 + 5x = 10
Add '10' to each side of the equation.
-10 + 10 + 5x = 10 + 10
Combine like terms: -10 + 10 = 0
0 + 5x = 10 + 10
5x = 10 + 10
Combine like terms: 10 + 10 = 20
5x = 20
Divide each side by '5'.
x = 4
Simplifying
x = 4